What Parish Are You From? : A Chicago Irish Community and Race Relations - McMahon, Eileen M. (Book collections on Project MUSE., 2015)
For Irish Americans as well as for Chicago's other ethnic groups, the local parish once formed the nucleus of daily life. Focusing on the parish of St. Sabina's in the southwest Chicago neighborhood of Auburn-Gresham, Eileen McMahon takes a penetrating look at the response of Catholic ethnics to life in twentieth-century America. She reveals the role the parish church played in achieving a cohesive and vital ethnic neighborhood and shows how ethno-religious distinctions gave way to racial differences as a central point of identity and conflict. For most of this century the parish served as an i.